Liquorice Extract and 18β-Glycyrrhetinic Acid Protect Against Experimental Pyrrolizidine Alkaloid-Induced Hepatotoxicity in Rats Through Inhibiting Cytochrome P450-Mediated Metabolic Activation - Zhangting Wang; Jiang Ma; Sheng Yao; Yisheng He; Kai-Kei Miu; Qingsu Xia; Peter P. Fu; Yang Ye; Ge Lin (Frontiers Media S.A., 2022)
Misuse of pyrrolizidine alkaloid (PA)-containing plants or consumption of PA-contaminated foodstuffs causes numerous poisoning cases in humans yearly, while effective therapeutic strategies are still limited. PA-induced liver injury was initiated by cytochrome P450 (CYP)-mediated metabolic activation and subsequent formation of adducts with cellular proteins. Liquorice, a hepato-protective herbal medicine, is commonly used concurrently with PA-containing herbs in many compound traditional Chinese medicine formulas, and no PA-poisoning cases have been reported with this combination. The present study aimed to investigate hepato-protective effects of liquorice aqueous extract (EX) and 18β-glycyrrhetinic acid (GA, the primary bioactive constituent of liquorice) against PA-induced hepatotoxicity and the underlying mechanism. Histopathological and biochemical analysis demonstrated that both single- and multiple-treatment of EX (500 mg/kg) or GA (50 mg/kg) significantly attenuated liver damage caused by retrorsine (RTS, a representative hepatotoxic PA). The formation of pyrrole-protein adducts was significantly reduced by single- (30.3% reduction in liver; 50.8% reduction in plasma) and multiple- (32.5% reduction in liver; 56.5% reduction in plasma) treatment of GA in rats. Single- and multiple-treatment of EX also decreased the formation of pyrrole-protein adducts, with 30.2 and 31.1% reduction in rat liver and 51.8 and 53.1% reduction in rat plasma, respectively. In addition, in vitro metabolism assay with rat liver microsomes demonstrated that GA reduced the formation of metabolic activation-derived pyrrole-glutathione conjugate in a dose-dependent manner with the estimated IC50 value of 5.07 µM. Further mechanism study showed that GA inhibited activities of CYPs, especially CYP3A1, the major CYP isoform responsible for the metabolic activation of RTS in rats. Enzymatic kinetic study revealed a competitive inhibition of rat CYP3A1 by GA. In conclusion, our findings demonstrated that both EX and GA exhibited significant hepato-protective effects against RTS-induced hepatotoxicity, mainly through the competitive inhibition of CYP-mediated metabolic activation of RTS.